TOCILIZUMAB AS MONOCLONAL ANTIBODY THERAPY IN OVERCOMING ACUTE RESPIRATORY DISTRESS SYNDROME IN COVID-19 PATIENTS - Muhammad Thifan Satyagraha; Graceanne Sheridan; Vito Etenio Ade Laryan; Gibran Chandra Syarif Hidayatullah (JIMKI: Jurnal Ilmiah Mahasiswa Kedokteran Indonesia, 2022)
Acute respiratory distress syndrome (ARDS) as a clinical manifestation of severe pneumonia is a major cause of death for patients with coronavirus disease 2019 (COVID-19) who are treated in intensive care units (ICU). ARDS is triggered by cytokine storm. Cytokine storm is characterized by an increased in proinflammatory cytokines such as IL-6, IL-1?, and IL-1?. Thus, IL-6 and IL-1 cytokine inhibitors in the form of monoclonal antibodies are needed to overcome this. This review of the scientific literature aims to identify the effect of monoclonal antibody therapy, which is focusing on the inhibitors of cytokines IL-6 (tocilizumab) and IL-1 (anakira) in patients with severe pneumonia caused by severe acute respiratory coronavirus-2 (SARS-CoV-2) ) with clinical manifestations in the form of ARDS. The design used in the form of scientific literature review. Articles were collected via Google Scholar search engine through several data sources (Pubmed, Sciencedirect, Nature, Proquest, and Springer Link). Inclusion criteria used were literature sources published between 2011 – 2020 in the form of research articles, systematic reviews, annual reports, and/or books. Meanwhile, the exclusion criterion used was literature sources under 2011. Based on article search results, tocilizumab can efficiently improve clinical status and reduce the mortality rate of COVID-19 patients with ARDS. Even so, tocilizumab can increase the risk of infection and the evidence obtained by the authors was not enough to support the administration of tocilizumab outside of clinical trials. Thus, the safety and side effects of monoclonal antibodies need to be further investigated.